Formulasi Dan Evaluasi Stabilitas Fisik Suspensi Ibuprofen Menggunakan Kombinasi Polimer Serbuk Gom Arab Dan Natrium Karboksimetilselulosa - Rina Wahyuni; Syofyan Syofyan; Septa Yunalti (Jurnal Farmasi Higea, 2017)
The research about formulation and evaluation of physical stability of ibuprofen suspension using arabic gom and  natrium carboxymethylcelulose as suspending agent had been done. Concentration of arabic gom and  natrium carboxymethylcelulose were 2.5 : 0.25, 5 : 0.5, 2.5 : 0.75 and 5 : 1 % for F1, F2, F3 and F4 respectinely. Evaluation of physical stability had been done  for 8 weeks, ie organoleptic, density, viscosity, volume of sedimentation, redispresion, pH, freeze thaw cycling, crystal growth and particle size distribution. Concentration of arabic gom and natrium carboxymethylcelulose had been influenced the physical stability of suspension.